2022
DOI: 10.3390/ma15020523
|View full text |Cite
|
Sign up to set email alerts
|

Starch as the Flame Retardant for Electrolytes in Lithium-Ion Cells

Abstract: The main purpose of this work is to illustrate the flame retardant properties of corn starch that is used as an additive to the classic electrolytes in lithium-ion cells. The advantages of using natural biomass include the increased biodegradability of the cell, compliance with the slogan of green chemistry, as well as the widespread availability and easy isolation of this ingredient. Due to the non-Newtonian properties of starch, it increases work safety and prevents the occurrence of thermal runaway as a she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In this situation, the possibility of battery explosions and fire increases. Many manufacturers of digital devices such as Lenovo and Apple have experienced substantial economic losses in the past decades as a result of thermal runaway issues [37,38]. Therefore, recognizing the thermal runaway of LIBs is essential to avoid all types of problems related to high temperatures.…”
Section: Thermal Runaway In Li-ion Cellsmentioning
confidence: 99%
“…In this situation, the possibility of battery explosions and fire increases. Many manufacturers of digital devices such as Lenovo and Apple have experienced substantial economic losses in the past decades as a result of thermal runaway issues [37,38]. Therefore, recognizing the thermal runaway of LIBs is essential to avoid all types of problems related to high temperatures.…”
Section: Thermal Runaway In Li-ion Cellsmentioning
confidence: 99%
“…Starch is an inexpensive and naturally occurring polysaccharide that exhibits charring properties, and has been considered as a potential biobased flame retardant for various different applications [25,26]. In this work, we investigated the possibility of replacing a commercial flame retardant (FR L069) used in LDPE formulations with a starch-based flame retardant, thereby reducing production costs and increasing both the safety and biodegradability of the final material.…”
Section: Preparation and Characterization Of The Blendsmentioning
confidence: 99%
“…The attribute had been employed in flame‐retardant applications, and it was found that whole grain starch addition to polymers was able to reduce the calorific value, the flame spread rate and the generation of smoke of the composites. [ 26–28 ] However, the fire resistance of pristine starch materials is not high enough for practical requirements; it is usually necessary to combine starch with other flame retardants to meet the practical application via synergistic effects. [ 29,30 ] To promote the mechanical performance of starch aerogels and endow them fire‐resistance simultaneously, borax was adopted based on the following consideration.…”
Section: Introductionmentioning
confidence: 99%